Simulative Impact Of Environment-Friendly Production Method Of Sarawak Pepper On Domestic And Export Supply - Wong, Swee Kiong (2007)

(untitled)
The need to protect the environment and utilize natural resources in more sustainable ways is gaining greater importance worldwide. Firms of any industry that do not keep abreast with this on-going trend of development in the global economy might sooner or later be swept away from the current highly competitive international market regime. Malaysia is an open economy that depends greatly on international trade for its national economic development. Pepper (Piper Nigrum L.), the King of spices, is grown in Malaysia predominantly (about 90%) for export market. To retain a significant market share for its pepper export, enhancing competitiveness in its pepper industry is a must. Hence, the objective of this study is to examine and assess the economic effects of cost of environmentally sustainable pepper production techniques and agricultural practices on production and export volumes in Malaysia.One of the major findings of this study is that chemical cost of pepper production has a significant negative effect on the domestic supply of both black and white pepper in Malaysia. Thus, to discourage farmers from using chemical inputs indiscriminately, increasing the chemical cost is suggested as a policy option. The simulation analysis reveals that environmental regulation to increase the chemical cost would enhance export market competitiveness of both black and white pepper in Malaysia. In fact, driven by the higher price incentive fetched for better quality environmental-friendly pepper produced, farmers start to produce more and thus the volumes of production and export would increase. In addition, welfare analysis also indicates that the welfare of pepper farmers will improve by adopting low cost sustainable pepper production methods. In short, promoting environmental-friendly pepper production in Malaysia should be given high priority. This is crucial to continue making Sarawak Pepper products marketable in the increasingly competitive international market. Moreover, by enhancing the competitiveness of the Malaysian pepper industry through the adoption of environmental-friendly pepper production methods will also help pepper farmers to meet a more stringent food safety, environmental and basic humanity requirements imposed in the international arena. This will ultimately help to improve the welfare of the Malaysian pepper farmers. This is particularly important so that pepper industry will continue to play its vital role as a major source of foreign exchange earnings besides being an important source of employment for some 74,710 households in the state of Sarawak.